The Roman province of Dalmatia during Constantine the Great and his heirs - Imamović, Mersiha (Historical Thought, 2025)
This study deals with political, economic and religious conditions in the province of Dalmatia during the reign of Constantine the Great and his successors. Political turmoil, followed by civil wars, was particularly significant during the II and III tetrarchies, but also afterwards. In all these events, the province of Dalmatia, unlike Pannonia, was spared war activities. Thanks to this, its economy could be safer to function. During the third tetrarchy, the doors of the free confession of faith were opened to Christians, resulting in the creation of other religious currents, which were also found in the provinces of Dalmatia and Pannonia. Constantine made reforms that included the province of Dalmatia. Certain administrative reforms of Dalmatia have also occurred during the time of Constantine’s heirs, marked by the general crisis and the growing uncertainty.